Challenges for dermatologists during the COVID-19 pandemic: A qualitative study - Matthew F. Helm, MD; Alexa B. Kimball, MD, MPH; Melissa Butt, MPH; Heather Stuckey, MEd, DEd; Heather Costigan, BS; Kanade Shinkai, MD, PhD; Arielle R. Nagler, MD (Wolters Kluwer, 2022)
Background:. Burnout is increasing in all fields of medicine, including dermatology. The coronavirus disease 2019 (COVID-19) pandemic presented new and additional challenges for dermatologists. Objective:. Dermatologists of different ages, areas of expertise, and practice settings were convened in 5 focus group to describe the impact of the COVID-19 pandemic on their clinical practice, working environment, and personal lives. Methods:. Qualitative analysis of the discussions w\s performed on the result of the 5 focus groups of dermatologists (n = 22). Groups were prompted with questions relating to their jobs, personal lives, teledermatology, and pandemic. Responses were recorded, transcribed, deidentified, and coded for recurring themes. The focus groups occurred via a secure videoconferencing platform between December 2020 and January 2021. All participants were currently practicing dermatology in a variety of setting including academic institutions, private practices, and multiple practice types. General dermatologists, residents in training, dermatologic surgeons, dermatopathologists, and dermatologists with significant administrative or educational duties were included. Results:. We identified 4 main themes from the focus group discussions regarding dermatologist and physician wellbeing during the COVID-19 pandemic: (1) adjusting to new administrative, staffing, and educational demands; (2) integration of work as a dermatologist with family life; (3) new technologies such as teledermatology; and (4) adjusting to change with redefining personal and professional priorities. Limitations:. The small number of participants in our convenience cohort disproportionately represented academic dermatologists. Impacts of regional COVID-19 vaccination rates and ideological differences in different geographical locations were not assessed. All of our participants were located in the United States. Physicians severely impacted by health or financial concerns may not have been able to participate in our study. We did not have a comparison group and did not measure or assess burnout in individual participants. Conclusion:. During the COVID-19 pandemic, there were common changes and stressors that dermatologists experienced, which affected physician wellbeing. Identifying and addressing these changes could offer the opportunity to improve the wellbeing of dermatologists.